PATRIARCH YOSYF SLIPYI AND TARAS SHEVCHENKO SCIENTIFIC SOCIETY - Рудницький , Л. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The previous year passed under the sign of Blazhennishyi Patriarch Yosyf Slipyi – an outstanding spiritual leader of the Ukrainian nation, a great Ukrainian and patriot, whose life and fate are a signpost for the present generation of citizens of the independent Ukrainian state. This article is about the role Blazhennishyi gave to Taras Shevchenko Scientific Society in shaping the national science, in persistent striving of his to include it in pan-European samples, in encouraging a new generation of Ukrainian scientists to serve their native people and native land with their work.